Advantages of Bacillus-based probiotics in poultry production - Ramlucken, U.; Lalloo, R.; Roets, Y.; Moonsamy, G.; van Rensburg, C. Jansen; Thantsha, M.S. (Livestock science, 2020)
•Bacillus spp. have several modes of action to be functional chicken probiotics.•Bacillus probiotics can be produced at high density with efficient and cost effective processes.•Bacillus spores are easily formulated into products using cost effective processes.•Bacillus probiotics have a longer shelf life and can be stored at warehouse conditions.•High spore viability during the incorporation of feed processes. Broiler chicken production is one of the most lucrative food production industries globally because of the demand for poultry products. Stringent regulations pertaining to the use of antibiotic growth promoters (AGP) in livestock production coupled with the changing consumer trends in terms of an increase in the consumtion of AGP-free meat pose a challenge to the poultry industry. Probiotics, specifically from the genus Bacillus, are emerging as a feasible solution to address this challenge because their spore-forming capabilities afford them several advantages over conventional probiotics. Success of these organisms has been attributed to their possession of a myriad of mechanisms that elicit probiotic effects, including among others, competitive exclusion of common poultry pathogens, improvement in digestion and absorption via the production of exogenous enzymes, improvement of intestinal morphology, immunomodulation, and the reduction of toxic compounds such as ammonia and aflatoxins. These effects reportedly reduce disease and mortality, improve feed efficiency up to 5%, enhance health, and assist in the environmental sustainability of poultry production. Bacillus spp. are easily isolated from environments and have up to 100% survivability in the harsh conditions of the gastrointestinal tract. Besides these important considerations, the key advantage for the use of Bacilli as feed probiotics is their robust nature pertaining to industrial production because of the high-density spore production, spores can be produced in excess of 1 × 1011 spores•mL−1. Furhtermore spores can retain approximately 90% viability during the probiotic harvesting process. In addition, these spores remain stable at a concentration of 1 × 109 spores•mL−1 when formulated into probiotic products, with a shelf life potential of 5 yr. Furthermore, spores retain their viability through the poultry feed manufacturing process. This review focuses on the unique beneficial characteristics of Bacillus spp. in both the production process of a viable probiotic product and the application thereof in the poultry industry.